2020
DOI: 10.1634/theoncologist.2020-0216
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk After Adjuvant Trastuzumab in Early Breast Cancer: An Italian Population-Based Cohort Study

Abstract: a,b on behalf of the FABIO working group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…For example, 6208 patients received T as part of their anti-cancer therapy experienced a significant short-term risk of cardiovascular diseases (hazard ratio (HR): 4.55; 95% CI: 2.58–8.01) compared to 12,416 matched patients who received chemotherapy without T or any other anti-Her2 treatment. 15 The OHERA prospective observational real-world study followed up 3733 patients with early BC on T-based adjuvant therapy. Symptomatic HF was reported in 2.8% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 6208 patients received T as part of their anti-cancer therapy experienced a significant short-term risk of cardiovascular diseases (hazard ratio (HR): 4.55; 95% CI: 2.58–8.01) compared to 12,416 matched patients who received chemotherapy without T or any other anti-Her2 treatment. 15 The OHERA prospective observational real-world study followed up 3733 patients with early BC on T-based adjuvant therapy. Symptomatic HF was reported in 2.8% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study dissected 1,248 axillary lymph nodes of 72 patients with breast cancer and found that axillary lymph nodes with a length of less than 5.1 mm still had a 10.1% metastasis rate, the LNM rate of 5.2-9.1 mm was 17.4%, and the LNM rate of 10.2-20.1 mm was 19.8%. In addition, the rate of LNM with a long diameter greater than 19 mm was 41%, and there was no correlation between lymph node metastasis and the size and histological grade of the primary tumor [ 22 , 23 ]. Combining with the literature, it can be concluded that axillary lymph node diameter > 1.2 cm can be classified as metastasis, but lymph nodes < 1.2 cm cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that most patients with breast cancer in Asia are diagnosed before menopause and have few cardiovascular risk factors. Additionally, despite trastuzumab inducing cardiovascular complications from several different perspectives, previous studies focused only on myocardial dysfunction, such as HF, whereas other vascular morbidities, including acute myocardial infarction (AMI) and stroke, were underestimated 8,12 . Most importantly, most nationwide cohort studies lack reliable multicentre validation to evaluate the accuracy of diagnosis, social habits and cancer stages 8,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, despite trastuzumab inducing cardiovascular complications from several different perspectives, previous studies focused only on myocardial dysfunction, such as HF, whereas other vascular morbidities, including acute myocardial infarction (AMI) and stroke, were underestimated. 8 , 12 Most importantly, most nationwide cohort studies lack reliable multicentre validation to evaluate the accuracy of diagnosis, social habits and cancer stages. 8 , 12 Therefore, it is mandatory to evaluate the incidences and clinical characteristics of trastuzumab‐induced cardiotoxicity in Asian women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation